Ada James: Conservative to Radical Woman in Life and Politics - Schade, Megan (My University, 2007)
This paper will discuss the changes in women?s lives in the early 20th century with the main focus on the political and social life of Ada James. While the political life of Ada James is covered in depth, the social life of Ada James has not been explored until now. The evidence shown in this paper will prove how through the influences of both her family and friends, Ada James progressed from a conservative woman to become one of the most radical women of her time, politically and personally. The sources used will be personal memoirs written by and to Ada James and the James family, and show how lives of women were improved through the women?s suffrage movement by giving women a voice in politics.
Keywords: James, Ada--Friends and associates.; James, Ada--Family.; James, Ada.; Suffragists--Wisconsin--Biography.; Suffrage--United States--History.